Semisolid systems containing propolis for the treatment of periodontal disease: In vitro release kinetics, syringeability, rheological, textural, and mucoadhesive properties - Bruschi, Marcos L.; Jones, David S.; Panzeri, Heitor; Gremião, Maria Palmira Daflon [UNESP]; De Freitas, Osvaldo; Lara, Elza H. G. (Wiley-Blackwell, 2007)
Formulations containing poloxamer 407 (P407), carbopol 934P (C934P), and propolis extract (PE) were designed for the treatment of periodontal disease. Gelation temperature, in vitro drug release, rheology, hardness, compressibility, adhesiveness, mucoadhesion, and syringeability of formulations were determined. Propolis release from formulations was controlled by the phenomenon of relaxation of polymer chains. Formulations exhibited pseudoplastic flow and low degrees of thixotropy or rheopexy. In most samples, increasing the concentration of C934P content significantly increased storage modulus (G'), loss modulus (G ''), and dynamic viscosity (n') at 5 degrees C, G '' exceeded G'. At 25 and 37 degrees C, n' of each formulation depended on the oscillatory frequency. Formulations showed thermoresponsive behavior, existing as a liquid at room temperature and gel at 34-37 degrees C. Increasing the C934P content or temperature significantly increased formulation hardness, compressibility, and adhesiveness. The greatest mucoadhesion was noted in the formulation containing 15% P407 (w/w) and 0.25% C934P (w/w). The work of syringeability values of all formulations were similar and very desirable with regard to ease of administration. The data obtained in these formulations indicate a potentially useful role in the treatment of periodontitis and suggest they are worthy of clinical evaluation. (c) 2007 Wiley-Liss, Inc.
Keywords: biodegradable polymers; buccal; natural products; mechanical properties; injectables; hydrogels; oral drug delivery